Design principles of collateral sensitivity-based dosing strategies - Linda B. S. Aulin (Nature Portfolio, 2021)
Collateral sensitivity-based antibiotic treatments may have the potential to limit the emergence of antimicrobial resistance. Here, the authors use mathematical modelling to study the effects of pathogen- and drug-specific characteristics for different treatment designs on bacterial population dynamics and resistance evolution.